PELATIHAN DESIGN THINKING SEBAGAI UPAYA MENINGKATKAN DAYA SAING IRT KERIPIK BAYAM BERKAH BAROKAH - Dian Ayu Liana Dewi; Muhammad Tahwin; Fajar sodiq; Rahma Auliya; Muhammad Ilham Al Asrori (LPPM Universitas Islam Darul 'Ulum Lamongan, 2025)
The purpose of this community service activity is to improve the competitiveness of the home industry (IRT)